Um olhar sistêmico do processo de tratamento da drogadicção na família - Brasil, Valéria Rocha (2005)
This study aims to understand how the family functions during the treatment process of the chemically dependent, within the complex thinking framework described by the author Edgard Morin. Therefore I carried out a longitudinal study with a family, whose 18 year old daughter was a drug addict and went through a specialized inpatient treatment. The family s configuration had the following characteristics: father s absence and his disqualification; an excessively present mother; addictions throughout the intergenerational system; constant incoherence in the children s rearing; difficulties in communicating; dispersed family; parents with relationship problems; the drug as a gathering factor and the children serving the purpose of filling the mother s emptiness. These aspects were coincident with functioning patters of other drug addicts families, described in parts of the literature about this subject. The clinic admission and post-treatment process of the dependent with her family was permeated by paradox, contradictory, ambiguous and antagonistic movements, which occurred simultaneously. Her reinsertion in the family represented dialogically moments of order and disturbance influencing each other mutually. The paradox is that the drug addiction becomes necessary for maintaining the status quo and the family s organization, so that the treatment and the changes of the addict are at the same time threatening and rewarding for the system at hand. The results show, that working on the chemical dependent s reinsertion in the family depends on understanding the complex relations that are established within this phenomenon, as well as on developing a very close treatment, which is sheltering and understanding, in order to build new possibilities of arrangements in the system, so that the threat and the losses do not surpass the gains achieved in the process of change.